Hubungan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada Pelajaran Tari Di Kelas X MAN 3 Kota Padang - Pebriza Armayeni; Yos Sudarman (FBS Universitas Negeri Padang, 2019)
This research aims to explain the correlation of learning motivation with the students’ learning outcome of the dance art in class X MAN 3 Padang. The problem of research was the difference of students’motivation in the class X MAN 3 Padang which were influenced by the teacher, materials, methods, media, and evaluation of the lesson. This research was quantitative research with correlational methods. Correlational research is a study tha measures the relationship between X dan Y variables. The research samples were 25 students of the class X-1 MAN 3 Padang. The instruments of the research were a questionnaire and a testof learning outcomes. The data were collected through interviews and observation as secondary data collection techniques. The results showed that there was a significant correlation between learning motivation and students’ learning outcomes at the dance subject at the MAN 3 Padang. It was proven by rxy value =0.759 which was higher than the rtable. 0.459. Thus,it has shown that the correlation between the two variables was significant. By proving this hypothesis, the learning motivation was demonstrated by attention, understanding diligence and confidence. The students’ learning outcome is improved when they are highly motivated to learn.